Electrocardiographic alterations in patients consuming synthetic cannabinoids. (March 2018) - Ozturk, Hayriye M; Erdogan, Mehmet; Alsancak, Yakup; Yarlioglues, Mikail; Duran, Mustafa; Boztas, M Hamid; Murat, Sani N; Ozturk, Selcuk
Introduction: The aim of this study was to investigate the electrocardiographic parameters in patients consuming synthetic cannabinoids. Methods: Thirty-five patients who were consuming synthetic cannabinoids were enrolled to the study, prospectively. The control group included 35 healthy age and sex-matched volunteers. The standard 12-lead surface electrocardiograms of the study population were recorded. P maximum (Pmax ), P minimum (Pmin ), P wave dispersion, interatrial duration, P wave area in D2 derivation, abnormal P terminal force in V1 derivation, heart rate, QT interval, corrected QT, QT dispersion, PR interval duration and macrovolt T-wave alternans were evaluated by two experienced cardiologists. The intra-observer and inter-observer variations for all measurements were non-significant. Results: Pmax and Pmin duration was not different between the groups ( p =0.96, p =0.15, respectively). However, P wave dispersion was higher in the patient group compared to control group (34±9.4, 29.5±6.6, p =0.02, respectively). QT interval was significantly higher in the patient group than the control group (380.3±25, 365.6±22.8, p =0.01, respectively). Besides, corrected QT was higher in the patient group compared to control group (415±36.8, 392±15.5, p =0.001, respectively). QT dispersion was also higher in the patient group than the control group (39.8±10.0, 29.2±5.4, p <0.001, respectively). Conclusion: Altered electrocardiography parameters linked with atrial and ventricular arrhythmia development may be observed in patients consuming synthetic cannabinoids. These patients should be evaluated regularly for cardiovascular disease and arrhythmia development. The electrocardiogram, which is a cheap and easy test to apply, can be used to determine the pro-arrythmic risk in patients consuming synthetic cannabinoids.